PENGEMBANGAN SISTEM PRESENSI KARYAWAN DENGAN TEKNOLOGI GPS BERBASIS WEB PADA PT BPR DANA MAKMUR BATAM - Sonny, Sonny; Rizki, Sestri Novia (Computer Science and Industrial Engineering, 2021)
Attendance record is very important because it can measure the level of someone’s dicipline. Any formal environments definitely use this method to monitor attendance. There are various methods of doing attendance, such as by biometric systems (fingerprint) or through by system. At the beginning, PT BPR Dana Makmur employee’s do attendance with a fingerprint machine. However the presence of coronavirus (Covid-19) caused changes of the attendance method in PT BPR Dana Makmur because the virus can be transmitted through fingerprint. From this problem, researchers tried to develop a web-based presence system to replace fingerprint methods. This application is expected to minimize the spread of the virus at PT BPR Dana Makmur or other company environtment.